2011
DOI: 10.1029/2011gl047167
|View full text |Cite
|
Sign up to set email alerts
|

The effect of particle shape on suspension viscosity and implications for magmatic flows

Abstract: 1] The rheology of crystal-bearing magma and lava depends on both the shape and volume fraction of the suspended crystals. We present the results of analogue rheometric experiments on monodisperse suspensions of solid particles in a Newtonian liquid, in which particle volume fraction and aspect ratio r p are varied systematically. We find that the effect of on viscosity is well captured by the Maron-Pierce model, and that this model is valid across the range of particle aspect ratios investigated (0.04 ≤ r p ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(130 citation statements)
references
References 32 publications
(46 reference statements)
2
127
1
Order By: Relevance
“…Consideration of non-Newtonian effects is essential for studying several environmental, industrial and biological phenomena, such as the spreading of muds in submarine settings [9]; the motion of natural suspensions containing sand, silt, clay and organic fractions [10,11]; debris flows in mountainous areas [12]; the propagation of pyroclastic flows produced by volcanic eruptions [13,14]; magma flow at sub-liquidus temperatures, owing to gas bubbles and to the presence of crystals [15]; the disposal of mine tailings in the minerals industry [16]; the flow of biomass slurries [17]; blood motion in arterioles [18]. In a number of instances, the fluid rheological behaviour is appropriately described by a Cross or Carreau-Yasuda model, but can be approximated over a certain range of shear rates by the simpler Ostwald-de Waele powerlaw model [19] if the yield stress is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of non-Newtonian effects is essential for studying several environmental, industrial and biological phenomena, such as the spreading of muds in submarine settings [9]; the motion of natural suspensions containing sand, silt, clay and organic fractions [10,11]; debris flows in mountainous areas [12]; the propagation of pyroclastic flows produced by volcanic eruptions [13,14]; magma flow at sub-liquidus temperatures, owing to gas bubbles and to the presence of crystals [15]; the disposal of mine tailings in the minerals industry [16]; the flow of biomass slurries [17]; blood motion in arterioles [18]. In a number of instances, the fluid rheological behaviour is appropriately described by a Cross or Carreau-Yasuda model, but can be approximated over a certain range of shear rates by the simpler Ostwald-de Waele powerlaw model [19] if the yield stress is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Other experiments were conducted on synthetic magmas at high temperature and pressure (Caricchi et al, 2007), which were then built into a 355 model that considered the influence of crystals on a suspension viscosity (Costa et al, 2009). For consistency, we have accounted for the effect of crystals (and bubbles) on the relative viscosity (η r cr ) using the equations of Mader et al (2013), which are mainly based on Mueller et al (2010aMueller et al ( , 2011. A series of steps are required to determine the relative effect of crystals, which take into account the shape, size and maximum packing fraction of crystals within the suspension.…”
Section: Rheology Of a Melt-crystal Suspensionmentioning
confidence: 99%
“…A number of papers investigated the effect of crystals on the apparent viscosity of the suspension 2 (e.g., Jeffery, 1922;Jeffrey and Acrivos, 1976;Mueller et al, 2010aMueller et al, , 2011. In particular, the experiments of Mueller et al (2010aMueller et al ( , 2011) examined a range of crystal sizes, aspect ratios and volume fraction to derive an empirical model for the apparent viscosity of a crystal-melt suspen-35 sion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marsh (1981) suggested that ϕ m should be 0.60 from petrographic evidence that there is an upper limit to the phenocryst content of lavas. Mueller et al (2011) experimented on the effect of crystal shape on relative viscosity and suggested that ϕ m may be less than 0.65, and ϕ m ε should be 2. Mueller did not take the size dispersion of the crystals into account, and it may increase ϕ m (Ishibashi and Sato, 2007).…”
Section: Viscosity Of the Extruded Lavamentioning
confidence: 99%